Network meta-analysis of patent foramen ovale management strategies in cryptogenic stroke. (3rd July 2018) - Saber, Hamidreza; Palla, Mohan; Kazemlou, Shaghayegh; Azarpazhooh, Mahmoud R.; Seraji-Bozorgzad, Navid; Behrouz, Réza
Abstract : Objective: To compare the outcomes of patent foramen ovale (PFO) closure vs antiplatelet agent (APA) vs oral anticoagulation therapy (OAT) for secondary prevention of stroke in patients with cryptogenic stroke, using direct and indirect evidence from existing randomized data. Methods: Relevant randomized controlled trials were identified by a systematic review. The efficacy outcome was stroke recurrence, and safety outcomes were atrial fibrillation and bleeding complications at the end of follow-up. Bayesian network meta-analysis was performed to calculate risk estimates and the rank probabilities using APA therapy as the reference. Results: In a network meta-analysis of 6 randomized controlled trials consisting of 3, 497 patients (1, 732 PFO closure, 1, 252 APA, 513 OAT), PFO closure and OAT were associated with lower rates of recurrent stroke (odds ratio [OR] 0.30, 95% credibility interval [CrI] 0.17–0.49 and OR 0.42, 95% CrI 0.22–0.78, respectively) with equal efficacy of OR 0.70 (95% CrI 0.37–1.49). PFO closure had the highest top rank probability of atrial fibrillation and OAT had the highest risk of bleeding complications. Conclusions: These findings suggest that closure and OAT may be equally effective in recurrent stroke prevention in patients with PFO. There is an increased risk of atrial fibrillation and bleeding with closure and OAT therapy, respectively. A randomized trial is needed to identify patients who would benefit most from each strategy.